Development of Mass Spectrometry Selected Reaction Monitoring Method for Quantitation and Pharmacokinetic Study of Stepharine in Rabbit Plasma. (20th February 2014) - Kopylov, Arthur T.; Kuznetsova, Ksenia G.; Mikhailova, Olga M.; Moshkin, Andrey G.; Turkin, Vladimir V.; Alimov, Andrei A.
Abstract : Highly sensitive liquid chromatography mass spectrometry method on triple quadrupole (QQQ) mass spectrometer was successfully applied for pharmacokinetic study of stepharine in rabbit plasma. Specific ion transitions of stepharine protonated precursor ion were selected and recorded in the certain retention time employing dynamic selected reaction monitoring mode. The developed method facilitated quantitative measurements of stepharine in plasma samples in linear range of five orders of magnitude with high accuracy and low standard deviation coefficient and pharmacokinetics parameters were calculated. The apparent volume of stepharine distribution (estimated as ratio of clearance to elimination rate constant, data not shown) allows us to assume that stepharine was extensively distributed throughout the body.